A comparative study on the AC/DC conductivity, dielectric and optical properties of polystyrene/graphene nanoplatelets (PS/GNP) and multi-walled carbon nanotube (PS/MWCNT) nanocomposites. (October 2020) - Mergen, Ömer Bahadır; Umut, Evrim; Arda, Ertan; Kara, Selim
Abstract: Polystyrene/graphene nanoplatelets (PS/GNP) and polystyrene/multi-walled carbon nanotube (PS/MWCNT) nanocomposites were prepared through solution mixing processing. The effect of carbon filler (CF) (GNP or MWCNT) doping on the DC/AC electrical conductivity, dielectric characteristics and optical parameters (absorption coefficient, α and band gap energy, E g ) of nanocomposites were investigated and compared for similar doping concentrations. The observed behavior of the DC surface conductivity for PS/CF nanocomposites was explained according to the classical percolation theory, where the percolation thresholds ( ϕ c ) for PS/GNP and PS/MWCNT nanocomposites were determined as 12.0 vol% and 3.81 vol% and the critical exponents ( t ) were calculated as 2.19 and 2.13, respectively. These results indicate that CFs create three dimensional CF network in PS matrix. The dielectric relaxation properties and the AC conductivity studied by means of Broadband Dielectric Spectroscopy (BDS) measurements, showed that the presence of carbon fillers significantly enhanced the capacitive/charge storage capabilities of the nanocomposites. The optical band gap energies ( E g ) of PS/GNP and PS/MWCNT nanocomposites were obtained by using Tauc method. From applicative point of view, with their enhanced dielectric and AC conductivity properties of the PS/GNP and PS/MWCNT nanocomposites have the potential to be used in energy storage and electromagnetic interference (EMI) shielding applications. Highlights: PS/GNP and PS/MWCNT nanocomposites were prepared by simple and efficient solution mixing and ultrasonic method. The effect of CF doping on the physical properties of nanocomposites were investigated and compared. Calculated the critical exponents indicate that CFs create three-dimensional CF network in PS matrix. The presence of CFs significantly enhanced the capacitive/charge storage capabilities of the nanocomposites. The optical band gap energies of PS/CF nanocomposites decreased with increasing CF doping..